A New Financing Model for Carbon Emission Reduction Projects: The Use of Carbon Emission Reduction Purchase Agreements (ERPA) in the Private Pension System - ŞEN, Gökhan; ÇELİK, Mehmet Yunus; ULUSOY, Tolga (Alinteri Zirai Bilimler Dergisi, 2019)
As a result of the awareness of global climate change, many studies have been carried out to avoid this situation. These studies have been carried out intensely since the protocol signed in Kyoto in 2005. Reduction of carbon dioxide emissions from engines operating on fossil fuels, the promotion of using the renewable natural sources such as wind, solar, etc. which are called clean energy, methane gas decompositions, and similar studies are some of these. As the studies increased, funding difficulties began to be seen in supporting the projects. In this context, especially project selection has started to gain importance. When the carbon emission reduction projects are examined, it is seen that forestry and especially forestation projects are very important. Especially, afforestation investments are very important in terms of increasing carbon sinks and many ecosystem services they provide are of great value. The aim of this study is to develop a new mechanism to create a source of financing for afforestation investments. In this context, the Private Pension System Funds was used as a fund-raising tool for the financing of afforestation investments. in this new mechanism, it was aimed that preventing climate change by making all actors gain income. With the implementation of this system, it is thought that the problems in the existing carbon markets will be prevented, the investments on afforestation will increase and also the environmental funds will become widespread.
Keywords: Agricultural, Veterinary and Food Sciences; Afforestation investment; Carbon markets; Carbon sink; Private pension system; Ziraat, Veterinerlik ve Gıda Bilimleri; 13. Climate action; 11. Sustainability; 1. No poverty; 15. Life on land; 7. Clean energy; 12. Responsible consumption